Extremely dangerous hypopituitarism related long QT syndrome and transient ST-segment elevation: A case report - Jia Zhang; Yingying Zou; Xiaoshu Chen; Jingye Pan; Haizhu Yu; Yi Wang; Yanran Wu; He Zou (SAGE Open Medical Case Reports, 2023)
Acquired long QT syndrome caused by hypopituitarism and transient ST-segment elevation has not been reported in cardiac arrest patients. We report a case of extremely dangerous acquired long QT syndrome and transient ST-segment elevation. A 44-year-old Chinese woman with renal failure experienced sudden cardiac arrest in the haemodialysis room. Subsequent electrocardiogram showed QT prolongation and transient ST-segment elevation. This patient’s medical history, subsequent laboratory results and pituitary magnetic resonance imaging suggested hypopituitarism. Transient ST-segment elevation on the electrocardiogram was considered to be caused by repeated direct current shocks. The patient was diagnosed with acquired long QT syndrome and was not taking any antiarrhythmic drugs. Her corrected QT interval normalized after hormone replacement therapy. This case highlights the importance of the awareness of hypopituitarism; early identification and intervention can prevent the occurrence of this life-threatening arrhythmia. ST-segment elevation is not always due to acute myocardial infarction, and a variety of other causes, especially electrical cardioversion, should be considered.